Radioembolization in the Office-Based Lab - St Amour, Edgar D. (Digestive Disease Interventions, 2021)
Interventional procedures have been performed on an outpatient basis in the hospital setting for many years, although there has been a clear trend toward performing these procedures in an outpatient facility, such as an ambulatory surgery center or office-based lab. And while this trend initially began with dialysis interventions and then endovascular interventions, interventional oncology is starting to catch on. Radioembolization has routinely been performed in an outpatient setting, and has recently gained traction in office-based labs due to new reimbursement codes, which became available in 2017. This article will outline the safety and feasibility, including economic considerations and demonstrated growth, of performing radioembolization in an office-based lab.
Keywords: office-based lab; outpatient; radioembolization